2022
DOI: 10.3389/fimmu.2022.1028440
|View full text |Cite
|
Sign up to set email alerts
|

Significance of macrophage infiltration in the prognosis of lung adenocarcinoma patients evaluated by scRNA and bulkRNA analysis

Abstract: PurposeTo investigate the significance of macrophage infiltration to the prognosis of lung adenocarcinoma.MethodsR language bioinformatics analysis technology, was used to obtain macrophage infiltration-related module genes through WGCNA (Weighted Gene Co-Expression Network Analysis). Marker genes of macrophage subtypes were identified using single-cell sequencing of lung adenocarcinoma tissue. Risk score models were constructed and validated using external data cohorts and clinical samples.ResultsAnalysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Some studies have suggested that silencing C1QTNF6 in LUAD cells can suppress the proliferation, migration and invasion of LUAD cells [ 51 ]. C1QTNF6 is a prognostic indicator for poor survival across many cancers including LUAD and one of the most relative genes of TAM [ 52 , 53 ]. However, there is still little knowledge about the function of C1QTNF6 in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that silencing C1QTNF6 in LUAD cells can suppress the proliferation, migration and invasion of LUAD cells [ 51 ]. C1QTNF6 is a prognostic indicator for poor survival across many cancers including LUAD and one of the most relative genes of TAM [ 52 , 53 ]. However, there is still little knowledge about the function of C1QTNF6 in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we selected 14 TME-related genes, including BIRC3, CELSR2, CXCL14, IL18, KLRB1, NPY1R, PSMB8, SCUBE2, STC2, CD1C, HLA-DPB1, GIMAP2, IRF1 and TNFAIP8, all of which were implicated in tumor progression and prognosis outcomes. BIRC3 is a member of the apoptosis inhibitor (IAP) family, with pro-survival and antiapoptotic effects in cancer cells ( 48 ). BIRC3 is associated with treatment resistance in BC; IL-1 upregulates BIRC3 and generates doxorubicin resistance in BC cells ( 49 ), thus BIRC3 appears to have important roles in the TME.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the presence of M2-type TAM is associated with pro-tumour activity, whereas the presence of M1-type TAM is associated with anti-tumour activity [38]. The association between TAM and tumour prognosis has been extensively studied, with numerous studies reported in colorectal, gastric, lung, ovarian, breast, pancreatic, and other cancers [39][40][41][42][43]. There is growing evidence that ferroptosis contributes to in ammatory and immune responses.…”
Section: Discussionmentioning
confidence: 99%